Nutritional Assessment of Children and Adolescents with Isolated Ventricular Septal Defects after Closure - Salama, Christine G.; El-Gharaz, Mohamed H.; Sharaf, Eman A.; Mostafa, Fatma A.; Eldesouky, Manar A. (South Eastern European Journal of Public Health, 2024)
Background: Children with congenital heart disease, including VSD, often start life with a normal birth weight. However, malnutrition and growth failure become apparent within the first few months. The energy intake and nutritional status of these children directly impact their growth, necessitating regular and meticulous follow- up from the moment of diagnosis, and extending for years after the defect has been corrected. The Aim: this study aimed to evaluate the nutritional status of children who have undergone surgical or interventional closure of isolated ventricular septal defects 6 to 12 months after closure. Methods: This study is a cross sectional observational included 50 patients were recruited form post cardiac interventional clinic (PCIC), Pediatric department Cairo university and October 6 university. All patients were subjected to Nutritional Assessment including objective and subjective global assessment, assessing length/height, weight, head circumference, BMI, skin fold thickness, and mid upper arm circumference. These parameters were plotted on WHO Z scores to detect malnutrition's type and degree. Nutritional Assessment by using the Subjective Global Assessment (SGA) form, that considers weight changes, food intake, functional status, and body composition, providing a holistic view of the child's nutritional health. Results: The mean age of the studied cases was 4.5 (±1.4 SD) with range (2.1-7.8) years, with 29 (58%) males. According to VSD size there were 8 (16%) moderate VSD and 42 (84%) large VSD. Membranous VSD was the most common type of VSD in 15 (30%). The mean age of VSD closure was 3.98y (±1.35 SD), according to method of closure. most of them were surgical 33 (66%) and 17 (34%) were interventional, The mean time interval between closure and assessment was 8 months (±2.14 SD). Among the studied cases according to subjective global assessment there were 8 (16%) A, 30 (60%) B and 12 (24%). Regarding weight for age on Z score 19 (38%) of the patients had moderate malnutrition lying bet (-2 to -3) and 1 patient (2%) had severe malnutrition less than (-3) on Zscore. Regarding MUAC 12 (24%) were moderately acute malnourished lying bet -2 to -3 and 10 (20%) were severely acute malnourished for age less than -3 on Z score. Regarding Ht for age on Z score 29 (58%) of the patients were above -2 on Z score while 42% were malnourished divided into 17 (34%) who suffers moderate stunting lies bet -2 to -3 on Z score and 4 (8%) had severe stunting for age less than -3. Conclusion: this study concludes that Malnutrition is still prevalent in patients after successful VSD closure and ongoing nutritional assessment is needed and SGA is a relevant tool in assessment of nutritional status of these children also Malnutrition in these patients is palpably multifactorial and not only due to the effect of VSD.